Are payers treating orphan drugs differently? - Joshua P. Cohen; Abigail Felix (Journal of Market Access & Health Policy)
Background: Some orphan drugs can cost hundreds of thousands of dollars annually per patient. As a result, payer sensitivity to the cost of orphan drugs is rising, particularly in light of increased numbers of new launches in recent years. In this article, we examine payer coverage in the United States, England and Wales, and the Netherlands of outpatient orphan drugs approved between 1983 and 2012, as well as the 11 most expensive orphan drugs. Methods: We collected data from drug regulatory agencies as well as payers and drug evaluation authorities. Results: We found that orphan drugs have more coverage restrictions than non-orphan drugs in all three jurisdictions. From an economic perspective, the fact that a drug is an orphan product or has a high per-unit price per se should not imply a special kind of evaluation by payers, or necessarily the imposition of more coverage restrictions. Conclusion: Payers should consider the same set of decision criteria that they do with respect to non-orphan drugs: disease severity, availability of treatment alternatives, level of unmet medical need, and cost-effectiveness, criteria that justifiably may be taken into account and traded off against one another in prescribing and reimbursement decisions for orphan drugs.